2020
DOI: 10.3390/polym12122775
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Activated Carbon Fibers from Oil Palm Trunk

Abstract: To develop more valuable application, oil palm trunk was successfully converted into activated carbon fibers (ACFs). An effective process of chemical treatment with dilute sulfuric acid was conducted to improve the thermal stability of primary fibers for further heating treatment. Carbon dioxide (CO2) was used as activator to produce much porous structure with various pore diameter. The specific surface area (SBET) and total pore volume (Vtotal) of resultant ACFs showed increasing trend as rise of activation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…93 Researchers have recently focused their attention on the utilisation of biomass as raw Environmental Science: Nano Critical review materials for the synthesis of activated carbon based on economic and environmental considerations. 94 Bio-wastes including oil-palm trunk fiber 95,96 palm shell, 97,98 coconut husk, 99 peanut hulls, 100 rice husk 101 and corncob 96 have been utilized for this purpose. With an eco-friendly motive, Wara et al reported on the synthesis of an adsorbent consisting of silver nanoparticle-functionalized activated carbon (Ag-AC) derived from bamboo.…”
Section: Environmental Science: Nano Critical Reviewmentioning
confidence: 99%
“…93 Researchers have recently focused their attention on the utilisation of biomass as raw Environmental Science: Nano Critical review materials for the synthesis of activated carbon based on economic and environmental considerations. 94 Bio-wastes including oil-palm trunk fiber 95,96 palm shell, 97,98 coconut husk, 99 peanut hulls, 100 rice husk 101 and corncob 96 have been utilized for this purpose. With an eco-friendly motive, Wara et al reported on the synthesis of an adsorbent consisting of silver nanoparticle-functionalized activated carbon (Ag-AC) derived from bamboo.…”
Section: Environmental Science: Nano Critical Reviewmentioning
confidence: 99%
“…The total pore volume was 0.41 cm 3 g −1 and the size of micropores was 0.69 nm under 900 °C for 60 min. Lin et al [ 46 ] used oil palm trunk as precursor to prepare ACFs using CO 2 activation method. The average pore size and the total pore volume of ACFs were 2.27 nm and 0.588 cm 3 g −1 , respectively, at temperature 900 °C for 90 min.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian penggunaan batang kelapa sawit untuk menjadi karbon aktif sejauh pengetahuan penulis, menggunakan aktivasi kimia dengan H 3 PO 4 , [3], ZnCl 2 /CO 2 [7], aktivasi fisika dengan gas dari kalsinasi batu kapur [8], dan gas CO 2 [9].…”
unclassified